The Autism Managing Eating Aversions and Limited Variety Plan vs Parent Education: A Randomized Clinical Trial - Sharp, William G.; Burrell, T. Lindsey; Berry, Rashelle C.; Stubbs, Kathryn H.; McCracken, Courtney E.; Gillespie, Scott E.; Scahill, Lawrence (The Journal of pediatrics, 2019)
To assess the feasibility and initial efficacy of a structured parent training program for children with autism spectrum disorder and moderate food selectivity. This 16-week randomized trial compared the Managing Eating Aversions and Limited variety (MEAL) Plan with parent education. MEAL Plan (10 core and 3 booster sessions) provided parents with nutrition education and strategies to structure meals and expand the child's diet. Parent education (10 sessions) provided information about autism without guidance on nutrition, meal structure, or diet. In addition to feasibility outcomes, primary efficacy outcomes included the Clinical Global Impression - Improvement scale and the Brief Autism Mealtime Behaviors Inventory. Grams consumed during a meal observation served as a secondary outcome. There were 38 eligible children (19 per group, 32 males). For MEAL Plan, attrition was <10% and attendance >80%. Therapists achieved >90% fidelity. At week 16, positive response rates on the Clinical Global Impression - Improvement scale were 47.4% for the MEAL Plan and 5.3% for parent education (P < .05). The adjusted mean difference (SE) on Brief Autism Mealtime Behaviors Inventory at week 16 was 7.04 (2.71) points (P = .01) in favor of MEAL Plan. For grams consumed, the adjusted standard mean difference (SE) was 30.76 (6.75), also in favor of MEAL Plan (P = .001). The MEAL Plan seems to be feasible, and preliminary efficacy results are encouraging. If further study replicates these results, the MEAL Plan could expand treatment options for children with autism spectrum disorder and moderate food selectivity. Clinicaltrials.gov: NCT02712281.